2021
DOI: 10.1016/j.sdentj.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different surface treatment methods on bond strength between fiber post and composite core material

Abstract: Purpose To assess the impact of different surface treatments on the push-out bond strength between fiber post and a composite resin core material. Material and methods Seventy-two glass-fiber posts were randomly assigned into six groups according to the method of surface treatment: Control (no treatment), silane, sandblasting, hydrofluoric acid, hydrogen peroxide, and hydrogen peroxide with sandblasting. Two posts from each group were inspected under a scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
2
17
0
5
Order By: Relevance
“…We observed greater BS in the cervical region of the root canal than in other regions. These results agree with the work of Alshahrani et al [ 17 ], in which the RelyX U200 cement showed higher BS values in the cervical third, regardless of the type of surface treatment of the post. The success of adhesive cementation inside the root canal, mainly at the apical level, can be compromised by several factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed greater BS in the cervical region of the root canal than in other regions. These results agree with the work of Alshahrani et al [ 17 ], in which the RelyX U200 cement showed higher BS values in the cervical third, regardless of the type of surface treatment of the post. The success of adhesive cementation inside the root canal, mainly at the apical level, can be compromised by several factors.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers disagree about the actual benefit of silanization in improving GFP retention, and other surface treatment alternatives have been investigated [ 11 , 14 ]. The roughness produced on the post surface with mechanical ( e.g ., blasting) [ 14 , 16 ] or chemical ( e.g ., application of hydrogen peroxide) methods [ 16 , 17 ] has been shown to improve the retention of GFPs fixed with resin cement by removing the matrix layer of epoxy resin and increasing the area of contact with the fibers that will be silanized [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, different methods, such as pull-out; push-out, and micro-tensile tests, have been used for the evaluation of the bond strength of posts cemented to natural tooth roots. The pull-out tensile bond strength testing of the cemented posts is considered superior to the other tests [ 17 , 18 , 19 ]. Previous studies have also used pull-out bond strength on natural teeth to clinically simulate the retention of endodontic post systems, and they have reported similar results [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to previous studies, which showed that the debonding of posts occurs when cement film thickness is increased [ 12 , 14 ]. It was proposed from the studies that when the cement layer is thinner, there will be less micro-porosities and polymerization stress, leading to higher retentive bond strength [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation